Whose responsibility is it to talk with children and young people about intersex/differences in sex development? Young people’s, caregivers’ and health professionals’ perspectives - Roen, Katrina; Lundberg, Tove; Hegarty, Peter; Liao, Lih-Mei (Frontiers in Urology, 2023)
Over the past two decades, there has been a shift from concealing diagnoses of sex development from impacted people to the broad principle of age-appropriate disclosure. This change is consistent with children’s rights and with general shifts towards giving children medical information and involving patients in medical decision-making. The present paper examines how health professionals, young people and caregivers with experience in this area talk about the process of telling children about a diagnosis relating to sex development. The focus is on (i) who is given the role of talking with children and young people about their medical condition and care in the context of a diagnosis relating to sex development and (ii) what strategies seem to work, and what dilemmas are encountered, in engaging children and young people in talk about their condition and healthcare. Qualitative semi-structured interviews were carried out with 32 health professionals, 28 caregivers and 12 young persons recruited in the UK and Sweden, and thematic analysis was undertaken. The analysis identifies strategies and dilemmas in communication and a widespread assumption that it is caregivers’ responsibility to talk with children / young people about the diagnosis. This assumption creates difficulties for all three parties. This paper raises concern about children / young people who, despite a more patient-centred care ethos, are nevertheless growing up with limited opportunities to learn to talk about intersex or differences in sex development with confidence. Learning to talk about this topic is one step towards shared decision-making in healthcare. A case is made for services to take clearer responsibility for developing a protocol for educating children and young people in ways that involve caregivers. Such a process would include relevant medical information as well as opportunities to explore preferred language and meaning and address concerns of living well with bodily differences.